PRINSIP-PRINSIP PENGEMBANGAN LITERASI DIGITAL DALAM PEMBELAJARAN - Putri Rusnadi, Riska; Izza, Nur; Yusuf, Narda; Istiqama; Nawir, Muhammad; Muhajir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digital transformation in education demands that students possess not only technical skills but also comprehensive digital literacy encompassing cognitive, social, and ethical aspects. This study aims to examine the principles of digital literacy development in learning to serve as a guideline for educators in designing effective and relevant instruction. The research method employed is a qualitative approach with a library research design. Data analysis techniques were carried out using content analysis through the stages of data reduction, data display, and conclusion drawing. The research results formulate five main principles for digital literacy development, namely: (1) relevance to student needs and real-world contexts; (2) integration within the curriculum; (3) sustainability as a lifelong learning process; (4) the cultivation of digital ethics; and (5) student empowerment as active and creative subjects. Research conclusions indicate that the systematic application of these principles can result in more effective and adaptive learning processes, equipping students with 21st-century skills. However, successful implementation still faces challenges regarding educator competence and technological facilities, which need to be addressed through systematic efforts from various stakeholders.